FACTORS INFLUENCING FARMERS' PERCEPTIONS OF AGRICULTURAL EXTENSION PERFORMANCE IN TAMAN DISTRICT PEMALANG DISTRICT - 'Adlih, Ba'itsuddin; Prayoga, Kadhung; Mariyono, Joko (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
A small number of agricultural extension workers and the budget for extension activities could affect farmers' perceptions of the performance of agricultural extension workers in Taman District, Pemalang Regency. The research was conducted to analyze farmers' perceptions of the performance of agricultural extension workers in Taman District, Pemalang Regency, and analyze the influencing factors. This research was conducted in January – February 2023 in Taman District, Pemalang Regency. The research method used was a survey with a proportionate stratified random sampling of 108 farmers. Data collection techniques in this study were observation, interviews, and documentation. The type of data was primary data including data on farmers' perceptions of the performance of agricultural extension agents and their factors, the identity of farmers and the identity of extension agents, regarding extension activities carried out, as well as their functions and duties and secondary data includes regional conditions and statistics and farmer documents. The analytical method used was descriptive analysis and multiple linear regression analysis. The results showed that farmers' perceptions of the performance of agricultural extension workers in Taman District, Pemalang Regency, obtained an average score of 1919 with an index score of 76.00% which means it was categorized excellent. The variables of farmer activity, farmer age, farmer education level, length of farming, and land area simultaneously influenced farmers' perceptions of the performance of agricultural extension agents in Taman District, Pemalang Regency.While only partially farmer activeness variable that influenced farmers' perceptions of the performance of agricultural extension workers in Taman District, Pemalang Regency. Suggestions that can be conveyed were that the government needs to increase the number of agricultural extension workers and provide a budget to improve their performance so that farmers can increase their prosperity.